Optical molecular imaging‐guided radiation therapy part 2: Integrated x‐ray and fluorescence molecular tomography. Issue 9 (21st July 2017) - Shi, Junwei; Udayakumar, Thirupandiyur S.; Wang, Zhiqun; Dogan, Nesrin; Pollack, Alan; Yang, Yidong
Abstract : Purpose: Differentiating tumor from its surrounding soft tissues is challenging for x‐ray computed tomography (CT). Fluorescence molecular tomography (FMT) can directly localize the internal tumors targeted with specific fluorescent probes. A FMT system was developed and integrated onto a CT‐guided irradiator to improve tumor localization for image‐guided radiation. Methods: The FMT system was aligned orthogonal to the cone‐beam CT onboard our previously developed image‐guided small animal arc radiation treatment system (iSMAART). Through rigorous physical registration, the onboard CT provides accurate surface contour which is used to generate three‐dimensional mesh for FMT reconstruction. During FMT experiments, a point laser source perpendicular to the rotating axis was used to excite the internal fluorophores. The normalized optical images from multiple projection angles were adopted for tomographic reconstruction. To investigate the accuracy of the FMT in locating the tumor and recovering its volume, in vivo experiments were conducted on two breast cancer models: MDA‐MB‐231 cancer xenograft on nude mice and 4T1 cancer xenograft on white mice. Both cancer cell lines overexpress the epidermal growth factor receptor (EGFR). A novel fluorescent poly(lactic‐co‐glycolic) acid (PLGA) nanoparticle conjugated with anti‐EGFR was intravenously injected to specifically target the breast cancer cells. Another ex vivo experiment on a mouse bearing a surgically implanted Indocyanine Green‐containing glass tube was conducted, to additionally validate the precision of FMT‐guided radiation therapy. Results: The FMT can accurately localize the single‐nodule breast tumors actively targeted with fluorescent nanoparticles with localization error < 0.5 mm calculated between the centers of mass of tumors in FMT and CT. The reconstructed tumor volume in FMT was significantly correlated with that in the iodinated contrast‐enhanced CT (R 2 = 0.94, P < 0.001). The FMT was able to guide focal radiation delivery with submillimeter accuracy. Conclusion: Using the tumor‐targeting fluorescent probes, the iSMAART with onboard FMT system can accurately differentiate tumors from their surrounding soft tissue, guide precise focal radiation delivery, and potentially assess tumor response in cancer research.